Effectiveness of daily directly observed treatment, short-course regimen among patients registered for treatment at an urban primary health center in Bengaluru - Huluvadi Shivalingaiah Anwith; Sreerama Reddy Kaushik; Ramanathan Thenambigai; M Madhusudan; Dandiganahalli Shivaram Priyanka; Nagaraj Deepthi; P S Karishma (Wolters Kluwer Medknow Publications, 2019)
Background: Tuberculosis (TB) is a major public health problem in India with high morbidity and mortality. As per the World Health Organization guidelines, the Revised National Tuberculosis Control Program introduced daily directly observed treatment, short-course (DOTS) regimen with a fixed-dose combination with weight bands. This study was undertaken to compare the effectiveness of daily DOTS regimen with intermittent regimen and to assess the proportion of adverse drug reactions in both groups. Materials and Methods: A descriptive study was conducted at a peripheral health institute under one of the TB Units in South Bengaluru. Participants registered for treatment during the third and fourth quarter of 2017 were selected using continuous sampling. Data were collected by case record analysis, structured interviews, and telephonic follow-up. Results: The study included 81 participants, with the mean age of 40 ± 16.1 years. Majority of the study participants 55 (67.9%) were male, and majority (38 [46.9%]) belonged to the upper-lower class. Forty-two (51.8%) of the study participants were on intermittent regimen, and 39 (48.1%) were on daily DOTS regimen. There was 100% sputum conversion at the end of treatment under both treatment regimens. A total of 36 (85.7%) participants under intermittent regimen and nine (23%) under daily regimen developed one or the other adverse drug reactions. The treatment success for participants under intermittent regimen was 38 (90.47%) and that for daily regimen was 35 (89.74%). However, there was no statistically significant difference between the two groups. Conclusion: Both daily and intermittent DOTS regimens are equally effective in TB treatment, but adverse drug reactions were more common with the intermittent regimen.